Impact of E-Service Quality, E-Word-Of-Mouth, and Subjective Norms on Purchase Intentions in The Tiktok Shop: A Study in Yogyakarta - Fikri Farhan; Ajeng Norma Khoirunnisa; Guruh Ghifar Zalzalah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2026)
Indonesia's embrace of the fourth industrial revolution highlights the transformative power of technology on business practices and consumer behavior. E-commerce platforms like TikTok Shop are increasingly preferred for online shopping. This study investigates the influence of electronic service quality, electronic word-of-mouth, and subjective norms on purchase intention within TikTok Shop. The study gathered data using an online questionnaire administered through Google Forms to 250 TikTok users between 18 and 24 years old living in Yogyakarta, an area recognized for its high level of digital technology adoption. Respondents were selected using a purposive sampling technique. The collected data were subsequently analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with the assistance of SmartPLS 3.2.9. The findings reveal significant positive effects of eSQ and subjective norms on purchase intention, while eWOM did not significantly influence. These insights contribute to a deeper understanding of consumer behavior in Indonesian e-commerce and social commerce.